Triangular gold nanoplates as saturable absorber for passively Q-switched fiber laser at 1.56 μm. (28th July 2021) - Kang, Zhe; Lv, Changjian; Liu, Mingyi; Li, Zhenrui; Qin, Weiping; Qin, Guanshi
Abstract: Wideband pulsed fiber lasers have been realized by using gold nanomaterials as saturable absorber (SAs). Compared to other morphologies, triangle gold nanoplates (TGNs) have multiple localized surface plasmon resonance peaks, which means that it can be used for construct wideband pulse laser. In this work, we propose and demonstrate an all-fiber passively Q-switched fiber laser at 1.56 μ m by using TGNs as SA. The modulation depth and saturation intensity of the TGNs SA measured at 1560 nm are 7.1% and 13.8 MW cm −2, respectively. By putting the TGN SA into the laser cavity pumped by a 980 nm laser diode, stable passively Q-switched laser at 1568 nm was achieved for a threshold pump power of 40 mW. The pulse duration decreases from 11.4 μ s to 4.2 μ s and the repetition rate increases from 12.5 kHz to 20 kHz with the increasing of the pump power from 40 mW to 75 mW. Our results indicate that the TGNs is a type of versatile broadband SA material for construct pulse lasers.